Description of the root anatomy of the primary molars using high resolution computed microtomography (Micro-CT). An analysis of three-dimensional root canal system - Vidi, Benedetta; Gil-Valcarcel, Ana María; Obispo-Diaz, Cristina; Sanchez-Jorge, Isabel; Mena-Álvarez, Jesús; Aragoneses-Lamas, Juan Manuel; Rico-Romano, Cristina (Frontiers in Dental Medicine, 2025)
Background/purposeThis study aimed to describe the root canal morphology of primary molars using Micro-CT and analyse the three-dimensional images of the internal root canal system.Material and methodsOne hundred and twenty extracted primary molars with one or more completed roots were scanned with Micro-CT. Three fixed heights of the roots were determined at axial level and the analysed criteria were: dentine thickness, diameter of roots canals, presence of lateral canals, isthmus and number of foramina. Vertucci's classification was also studied.ResultsVertucci Type I was more prevalent in palatal and mesio-buccal root of superior molar and distal root of inferior molars. Type IV was more frequent in the mesial root. Dentine thickness was studied at three levels and for all the surfaces of the root canal. In the mesiobuccal root, in the middle and apical third, the mean in the upper molars is significantly higher than in the lower molars. The mesio-lingual canal has the major mean in mesio-distal and bucco-lingual diameter at coronal third. Isthmus were found mostly in the mesial root in all three levels. The high number of foramina and lateral canals were located at apical third of the mesial and mesio-buccal roots.ConclusionThis study showed the complexity and variability of the root canal morphology of primary molars. The Micro-CT images gave important information about the internal anatomy of the primary molars.